Importance of screening and identification of alloantibodies in multi-transfused patients of thalassemia major. - Hazra, Subhajit; Parveen, Pauline Ara; Lyngdoh, Banduriap; Moi, Pratima; Bagdi, Sunita; Ghosh, Sulekha; Ghosh, Tapan Kumar (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction: Thalassemia is a form of inherited autosomal recessive blood disorders characterized by abnormal formation of hemoglobin. These patientsneed blood transfusion on regular basis to maintain the hemoglobin level in the body.The frequent transfusions received by thalassemia major patients, expose them to the risk of contracting infectious diseases, and development of complication such as iron overload and alloimmunization. The production of antibodies against such alloimmunization induces further hemolysis. Subject and methodology: The main objective of the study was to find out clinically significant antibodies in multi-transfused thalassemiamajor patients to prevent hemolysis and to reduce frequency of blood transfusion there by reducing morbidity and mortality. A prospective and observational study comprising of total 205 thalassemic patients were included in the study (females 99 and males 106) in the age ranging from3to 43 years who had received more than 10 units of blood within one year. Majority of them were β thalassemia major followed by Eβ and sickle cell disease.Apart from ABO and Rh grouping and issuing of blood by proper crossmatching the alloantibodies were detected by using 3 cell and 11 cell panel by gel technique.Alloantibodies against Rh phenotypes were more than 90%. Discussion and conclusion:Findingof unexpected antibodies must be a part of all pretransfusion testing procedure which will help to accomplish more effective and uneventful blood transfusionof multi-transfused thalassemia patient. Production of alloantibodiesinmulti-transfused thalassemia patients can be prevented by screening for minor blood groups from beginning in addition to ABO and Rh grouping. International Journal of Human and Health Sciences Vol. 05 No. 02 April’21 Page: 230-234